2014
DOI: 10.1007/s10140-014-1278-1
|View full text |Cite
|
Sign up to set email alerts
|

Wrist fractures: sensitivity of radiography, prevalence, and patterns in MDCT

Abstract: The aims of this study are to evaluate diagnostic performance of conventional radiographs for wrist fractures using multidetector computerized tomography (MDCT) as a reference standard, to determine prevalence, demographic risk factors including age and sex, and associations among various wrist fractures. A retrospective study was performed, finding a total 455 patients (457 wrists) who had wrist trauma and who had undergone a radiography and subsequent MDCT examination during a 45-month period. The MDCT and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 18 publications
1
30
0
4
Order By: Relevance
“…The American College of Radiologists recommended MRI as the best second‐line investigation, however, since then the number of MRIs performed in scaphoid fracture diagnosis has not significantly increased despite MRI changing the management of clinically suspected scaphoid fracture cases in 92% of cases . Additionally, it is reported that in approximately 10% of cases scaphoid fractures are concomitant with other fractures of the hand or wrist, fractures which are often radiographically occult, such as capitate and lunate fractures . Frequently, the signs and symptoms of clinically suspected scaphoid fractures are due to other bony or soft tissue injuries, as in 50.0% of our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The American College of Radiologists recommended MRI as the best second‐line investigation, however, since then the number of MRIs performed in scaphoid fracture diagnosis has not significantly increased despite MRI changing the management of clinically suspected scaphoid fracture cases in 92% of cases . Additionally, it is reported that in approximately 10% of cases scaphoid fractures are concomitant with other fractures of the hand or wrist, fractures which are often radiographically occult, such as capitate and lunate fractures . Frequently, the signs and symptoms of clinically suspected scaphoid fractures are due to other bony or soft tissue injuries, as in 50.0% of our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Balci et al, examined diagnostic performance of conventional radiographs for wrist fractures using multidetector CT as a reference standard 1 . They revealed that sensitivity of x-ray for radius fracture is only 72.8% and 80% for ulna fracture.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of evidence for the utility of sonographic (US) examination for detecting of distal forearm fracture in adults. Standard imaging tool for the diagnosis of distal forearm fracture is X-ray, however it's sensitivity is low 1, 2…”
Section: Introductionmentioning
confidence: 99%
“…Wrist fractures may be occult on the standard dorsoplantar, oblique, and lateral wrist radiographs warranting further imaging for patients with persistent clinical suspicion for a fracture [10].…”
Section: Hand and Wristmentioning
confidence: 99%